Assessing Benefit Portability for International Migrant Workers : A Review of the Germany-Turkey Bilateral Social Security Agreement - Holzmann, Robert (World Bank, Washington, DC, 2016)
The portability of social benefits is gaining importance given the increasing share of individuals working at least part of their life outside their home country. Bilateral social security agreements (BSSAs) are considered a crucial approach to establishing portability, but the functionality and effectiveness of these agreements have not yet been investigated; thus importance guidance for policy makers in migrant-sending and migrant-receiving countries is missing. To shed light on how BSSAs work in practice, this document is part of a series providing information and lessons from studies of portability in four diverse but comparable corridors: Austria-Turkey, Germany-Turkey, Belgium-Morocco, and France-Morocco. A summary policy paper draws broader conclusions and offers overarching policy recommendations. This report looks specifically into the working of the Germany-Turkey corridor. Findings suggest that the BSSA between Germany and Turkey is broadly working well, with no main substantive issues in the area of pension portability and few minor substantive issues concerning health care portability and financing. Some process issues around information and automation of information exchange are recognized and are beginning to be addressed.